2021
DOI: 10.3390/ijerph19010126
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physical Activity Compared to the Situation before the Outbreak of COVID-19 in Korea

Abstract: The purpose of this study is to examine changes in physical activity in Korean society, after the outbreak of COVID-19. Method This study was conducted using the Korean Community Health Survey conducted in 2019 and 2020. Subjects that have been diagnosed with hypertension and diabetes were excluded; a total of 355,914 cases were involved for analysis. In terms of the analysis method, General Linear Model (GLM) was conducted to examine the changes in physical activities in 2019 and 2020 depending on the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…48) In Korea, a study based on the Korean Community Health Survey conducted in 2019 and 2020 revealed a decrease in the time spent on moderate-intensity physical activity, which was more than 20 minutes per week for both men and women. 49) In a study of 834 adults in Korea, the number of daily steps measured by smartphone applications before and after the COVID-19 pandemic decreased by more than 10% from approximately 6,747 to 5,812. 50) A study involving 1,154 adults in Korea reported that the average daily sitting time increased by 44 minutes after the pandemic.…”
Section: Pandemic and Physical Activitymentioning
confidence: 99%
“…48) In Korea, a study based on the Korean Community Health Survey conducted in 2019 and 2020 revealed a decrease in the time spent on moderate-intensity physical activity, which was more than 20 minutes per week for both men and women. 49) In a study of 834 adults in Korea, the number of daily steps measured by smartphone applications before and after the COVID-19 pandemic decreased by more than 10% from approximately 6,747 to 5,812. 50) A study involving 1,154 adults in Korea reported that the average daily sitting time increased by 44 minutes after the pandemic.…”
Section: Pandemic and Physical Activitymentioning
confidence: 99%
“…Meanwhile, moderate-intensity physical activity was significantly reduced in all groups. On the other hand, while adult men and women did not show a significant difference in walking activity, a significant decrease was found in walking activity in older men and a significant increase in elderly women (Lee et al, 2021). Despite different determinants of physical inactivity in adolescents during Covid-19 restrictions in Europe and Latin America, a high percentage of physical inactivity was observed in the population before and during the Covid-19 pandemic (Ruiz-Roso et al, 2020).…”
Section: Discussionmentioning
confidence: 77%
“…Although it is well known that regular physical activity has a strong effect on the immune system and fights many of the chronic diseases that increase the risk of death from COVID-19 (Clemente-Suarez et al, 2022), restrictions imposed to prevent the spread of the virus, stay-at-home restrictions, parks, closure of gyms and fitness centres and public health recommendations have led to a decrease in daily physical activity (Kenyon, 2020). Studies report decreases in physical activity level during the COVID-19 pandemic among adults in the USA (Meyer et al, 2020;Yang & Koenigstorfer, 2020), Australian (Gallo et al, 2020), Italy (Franco et al, 2021;Galle et al, 2020;Luciano et al, 2021), Spain (Martinez-de-Quel et al, 2021), Israel (Dor-Haim et al, 2021), Türkiye (Girgin & Okudan, 2021;Tural, 2020), the UK (Hamrouni et al, 2021), Russia (Smirnova et al, 2021), Korea (Lee et al, 2021), Canada (Bertrand et al, 2021;Lesser & Nienhuis, 2020) and Iran (Amini et al, 2020). Walking activity times, high and moderate physical activity decreased for all participants in Korea after social distancing due to COVID-19, the pattern of change in physical activities differed according to spouses, education levels and economic activities (Lee et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, among the population of England, the rate of physical activity declined by 30% in 2020 compared to that in the period from 2016 to 2019 [ 4 ]. In Korea, the time spent in high-intensity PA decreased in all age and gender groups in 2020 compared to that of 2019 according to the Korean Community Health Survey data [ 5 ]. World Health Organization (WHO) reported that lack of physical activity (PA) is one of the risk factors for chronic diseases such as cancers, cardiovascular disease burden, and even death [ 6 ].…”
Section: Introductionmentioning
confidence: 99%